Study on Preparation and Properties of InN Films on Self-Supporting Diamond Substrates Under Different Nitrogen Flows - Wang, Shuaijie; Qin, Fuwen; Bai, Yizhen; Zhang, Dong (Frontiers in Materials, 2020)
Several InN film samples with superb properties were prepared on a self-supporting diamond substrate for different nitrogen flow rates using an electron cyclotron resonance plasma-enhanced metal-organic chemical vapor deposition (ECR-PEMOCVD) system. After the InN film samples were obtained, the samples were characterized via reflected high-energy electron diffraction (RHEED), X-ray diffraction (XRD), scanning electron microscopy (SEM), atomic force microscope (AFM), and electron probe micro-analysis (EPMA) to study the effect of the nitrogen flow on the quality of the InN films. The experimental results show that the variation in the nitrogen flow has a great impact on the preferential growth of the (0002) crystal plane of the InN thin-film. By increasing the nitrogen flow moderately, the crystal quality of the film is improved. Under the growth condition of appropriate nitrogen flow, InN thin-films with a preferred orientation along the c-axis can be obtained, and the surface of the resulting InN thin-films is relatively flat. However, a high nitrogen flow does not improve the film crystal quality. The results of the experiment and of the analysis show that the InN films prepared with a nitrogen flow rate of 80 sccm have an excellent preferential orientation. The result of the EPMA test shows that the percentages of the In and N atoms in the prepared film samples are close to a ratio of 1:1, and a small amount of metal In droplets is present. In addition, the InN thin-films prepared in such condition have an excellent surface morphology and composition.